Response of intensive and thermophysical properties of a Pulsatile blood through Stenosed artery subject to drug delivery - Anthuvan Ezhilarasi P; Dhivya Mohanavel (Heliyon)
A numerical attempt has been initiated to analyze an unsteady pulsatile blood flow of ternary nanoparticles (Au, GO, and Fe3O4) in a two-dimensional model through tapered arterial stenosis when a magnetic field is present. The most significant motivations for treating tri-hybrid nanoparticles as nanomaterials is their exceptional antimicrobial and biocompatible properties, which enhance thermal conductivity and facilitate nano-drug delivery. The semi-analytical approach used in this model involves solving the governing Navier-Stokes equations. At the same time, computational simulations are performed using the shooting method with the assistance of a MATLAB solver. Furthermore, the effects of flow-related parameters such as wall shear stress and resistive impedance on velocity distribution have been discussed. The findings indicate that the wall shear stress rises with increasing Womersley parameters, whereas the flow velocity diminishes with higher magnetic parameter values. Moreover, sensitivity analysis is elucidated to ascertain the interrelated impacts of the key parameters. In addition, the current study also validated the existing results and it was found to have a good agreement. Major exploration of this study reveals that the obtained results may have implications for cancer treatment, tumor therapy, heart surgery, and other hyperthermia therapies.